Machining induced tribological investigations in sustainable milling of Hardox 500 steel: A new approach of measurement science. (30th September 2022) - Kuntoglu, Mustafa
Highlights: Presents a new approach for determining the tribological aspects of machining of Hardox 500 under sustainable conditions. Four different cooling and lubricating regimes were used to measure the machinability characteristics. Liquid CO2, MQL, flood and dry mediums were tried to understand the underlying mechanism of milling operation of Hardox 500. Hardox 500 is important to observe machining quality as per its place in the industry. Cryogenic machining was found as the effective way considering various machining characteristics in milling. Abstract: Hardox 500 is known as hard-to-cut steel possessing supreme abrasive wear resistance that makes it suitable for industrial applications especially for transportation. However, such properties limit the machinability of this low alloy, martensitic material in addition to being sensitive to thermal loading. Therefore, this study purposes to improve the machinability index of Hardox 500 steel by questioning the tribological influence of the various cooling and lubricating environments during milling operation. In this direction, dry, pure-MQL, conventional flooding and LN2 based cryogenic mediums were tested while observing tool wear, surface roughness and topography, cutting temperature and chips morphology. Seemingly, cryogenic environment suppresses the thermal effects while cutting with improving tool wear resistance, surface quality of the part and chips morphology, in comparison with other regimes. A supreme enhancement in the flank wear (114 %), cutting temperature (319 %) and surface roughness (152 %) were achieved by using cryogenic cooling over dry regime. Obtained findings were discussed within the framework of the tribological performance of the sustainable lubri-cooling regimes.